Framing Analysis of Jakarta Air Pollution News Construction of Tirto.id and Tribunnews.com Media - Baswedan, Fauzi; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to pay attention to the process of publishing news in online media. News is consumption for the public to find out the latest information related to all kinds of information in Indonesia. This research uses the framing analysis methodology initiated by Robert Ethman, framing is the process of a media framing a story that is broadcast to the audience, this process will influence the perception and direction of the audience's opinion regarding the news that is spread. Data collection in this research looked at 2 of the many online media in Indonesia, namely Tirto.id and Tribunnew.com. The case selection that has become a hot topic of conversation in the public environment is air pollution which has a negative impact on public health. The results obtained based on this research are that there are pros and cons for the media regarding the way the government works in dealing with Jakarta's air pollution. The framing taken by Tirto.id is towards a counter-diction position or criticism of the government's way of dealing with this problem, while Tribunnews.com takes framing steps that lead to pro-government action in handling this problem. The hope of this research is to help the public to choose the characteristics of the media they will choose to consume, just as there are groups of people who have the idea to criticize and not infrequently also those who always think that the choice of way of dealing with city problems carried out by the government is appropriate and are just waiting for the results of the handling that.